The Changes in Online News Headlines in 2013 and 2023: A Discourse Analysis Study - Zulferdi, Lazuar Azmi; Suswandi, Irwan (Humanis; Vol 28 No 2 (2024)DO - 10.24843/JH.2024.v28.i02.p06, 2024)
The development of journalism is not only related to the media changing from paper to digital. However, the high demand for online news production and the speed of publication also influence the changes in online news headlines. This research discusses the changes in online news headlines in 2013 and 2023. This study employed qualitative-quantitative methodology. The uninvolved conversation observation technique was applied in collecting the data, while the distributional and identity methods were used to analyze the data. The data source was obtained from Detik.com during the first weeks of 2013 and 2023. The theory used was Van Dijk's critical discourse theory. The results demonstrated that the changes in news headlines in 2013 and 2023 included differences in the number of words, type of sentence, syntactic patterns, use of affixations, use of prepositions, use of punctuation, negation, mention of names, presence of interjections, presence of slang words, and use of onomatopoeic.